Optimizing tissue stewardship in non-small cell lung cancer to support molecular characterization and treatment selection: statement from a working group of thoracic pathologists. - Kerr, Keith M.; Bubendorf, Lukas; Lopez-Rios, Fernando; Khalil, Farah; Roy-Chowdhuri, Sinchita; Joubert, Philippe; Hartmann, Arndt; Guerini-Rocco, Elena; Yatabe, Yasushi; Hofman, Paul; Cooper, Wendy A.; Dacic, Sanja (Histopathology, 2024)
Many patients with non-small cell lung cancer do not receive guideline-recommended, biomarker-directed therapy, despite the potential for improved clinical outcomes. Access to timely, accurate, and comprehensive molecular profiling, including targetable protein overexpression, is essential to allow fully informed treatment decisions to be taken. In turn, this requires optimal tissue management to protect and maximize the use of this precious finite resource. Here, a group of leading thoracic pathologists recommend factors to consider for optimal tissue management. Starting from when lung cancer is first suspected, keeping predictive biomarker testing in the front of the mind should drive the development of practices and procedures that conserve tissue appropriately to support molecular characterization and treatment selection.
EVALuna2:542959